Application of complementary analytical tools to support interpretation of polymer-electrolyte-membrane fuel cell impedance data - Roy, S.K.; Hagelin-Weaver, H.; Orazem. M.E.
A series of ex situ techniques, including scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction, and inductively coupled plasma-mass spectroscopy were used to study morphological and chemical changes associated with the aging of a membrane electrode assembly in a olymer-electrolyte-membrane fuel cell. These results were correlated with the results of in situ electrochemical measurements, including measurement of steady-state polarization curves and electrochemical impedance spectroscopy. The results support the premise that the low-frequency inductive features seen in the impedance response provide information useful for understanding phenomena, such as platinum oxidation, that lead to reduction of fuel cell performance. The reduction in electrochemically active surface area, obtained from the high-frequency part of the impedance response, was consistent with the observed agglomeration of platinum particles and platinum oxidation.
Keywords: X-RAY DIFFRACTION; X-RAY PHOTOELECTRON SPECTROSCOPY; TRANSMISSION ELECTRON MICROSCOPY; SCANNING ELECTRON MICROSCOPY; CAPACITANCE; IMPEDANCE SPECTROSCOPY